2019
DOI: 10.3892/ol.2019.11147
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of LINC01140 is associated with adverse features of breast cancer

Abstract: Breast cancer (BC) is one of the most dangerous malignant diseases among women. A growing amount of evidence has suggested that long non-coding RNAs participate in the development and progression of BC and may potentially serve as therapeutic targets or prognostic markers for the disease. A previous study demonstrated that long intergenic non-protein coding RNA 01140 (LINC01140) was prominently correlated with overall survival in patients with gastric cancer. However, the function of LINC01140 in BC has not ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 31 publications
2
16
0
Order By: Relevance
“…Marina et al demonstrated that LINC01140 was an important regulator of proliferation and inflammation in human lung fibroblasts [ 42 ]. LINC01140 may be a potential biomarker for the prognosis of patients with breast cancer [ 43 ] and gastric cancer [ 44 ]. However, there has no study show the connection between LINC01140 and LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…Marina et al demonstrated that LINC01140 was an important regulator of proliferation and inflammation in human lung fibroblasts [ 42 ]. LINC01140 may be a potential biomarker for the prognosis of patients with breast cancer [ 43 ] and gastric cancer [ 44 ]. However, there has no study show the connection between LINC01140 and LUAD.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent study has reported that LINC01140 appears to be a tumor suppressor. 28 Specifically, LINC01140 is downregulated in breast cancer tissues, and on its overexpression, it ultimately affects the epithelial-mesenchymal transition (EMT) process of cells by adsorbing miR-200b and miR-200c, resulting in an antitumor effect. 28 In addition, another study has found that LINC01140 may inhibit the malignant phenotype of glioma cells by modulating the miR-199a-3p/ZHX1 signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Then, significant ternary relationships (DEmiRNA-DEmRNA-DElncRNA) were selected, and the top degrees of lncRNA in these were thought to be the key lncRNAs, and the mRNA interactions with these key lncRNAs were explored in Although lncRNA-associated research is limited, the key lncRNAs obtained above have been found to be related to some other diseases, for example, downregulation of LINC01140 is associated with adverse features of breast cancer, 37 and significantly correlates with overall survival in gastric cancer patients. 38 High MSC-AS1 expression was correlated with poorer prognosis in patients with pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Although lncRNA-associated research is limited, the key lncRNAs obtained above have been found to be related to some other diseases, for example, down-regulation of LINC01140 is associated with adverse features of breast cancer, 37 and significantly correlates with overall survival in gastric cancer patients. 38 High MSC-AS1 expression was correlated with poorer prognosis in patients with pancreatic ductal adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%